A Building as a Catalyst for Change: the New British Library Centre for Conservation - Shenton, Helen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
The new Centre for Conservation at the British Library (BLCC) opened in London this year. This 2600 square metre, purpose-built Centre is connected to the main British Library by a new public terrace and is adjacent to the new St Pancras Eurostar station opening in November 2007. The Centre houses state-of-the-art book conservation studios and sound preservation studios, together with facilities for an extensive training and public outreach programme. The public programme includes a permanent, free exhibition and education suite at the entrance to the new Centre, linked to the rotation of iconic collection items within the BL’s Treasures Gallery. There are to be free, behind-the-scenes tours of the conservation studios for the public as well as demonstrations, workshops and talks. The professional outreach includes partnering with the University of the Arts on setting up a new two-year Foundation Degree in Book Conservation, setting up funded internships for book and sound preservation, and steps to furthering the BL in conservation research. From the beginning, there were three main, intertwined elements at the core of the Centre for Conservation project, namely construction, fund-raising and a ‘change programme’. The paper describes the construction project and highlights features such as the ‘floating’ sound studios, the natural north light that bathes the majority of the conservation studios and describes how the needs of visitors and circulation were anticipated. Secondly it describes the nature of the fund-raising for the €19.65 (£13.25) million project, which was the first such capital fund-raising project undertaken by the BL. The money has been raised from a combination of public and private sources. The mixture of conservation, professional training and public access has been key to the success in raising the funds. Thirdly, the paper describes how the impetus for providing appropriate accommodation for those areas not incorporated into the St Pancras building in the late 1990s, was used as a catalyst for change. The space was designed to engender different ways of working and the very process of developing the project was used to develop people by working in different ways. This is a modernisation and ‘cultural change’ project, whereby the challenge has been to keep the best of the old (the artisanship, hand craft skills and technical expertise) and create the best of the new (updating conservation techniques, developing new skills commensurate with the needs of the collections, evolving organisational changes).